Young, open and international: the impact of search strategies on the internationalization of new ventures - Jörg Zimmermann; Christoph Grimpe; Wolfgang Sofka (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
Young firms with the ability to internationalize early and decisively have received much attention in recent academic discussion. However, relatively little is known about the underlying processes that enable them to skip several stages of the internationalization process. We contribute to this research stream by establishing theoretical links with the emerging open innovation paradigm of firms optimizing their R&D activities by interconnecting them with external partners such as leading customers, universities or specialized suppliers. Based on a sample of more than 2,500 firms in Germany we contrast young and mature firms with regard to the effect of open innovation strategies on internationalization performance. Our results show that both the breadth and depth of search strategies for external knowledge help young firms to enter international markets. Once they have entered these markets, though, the drivers for success seem to shift from general knowledge sourcing to targeted and specific ones.
Keywords: 330; New ventures; internationalization; innovation; search strategies; entrepreneurship; Unternehmensgründung; Multinationales Unternehmen; Innovation; Open Source; Informationsverhalten; Suchtheorie; Unternehmer; Deutschland